Molecular Quantification of Total and Toxigenic Microcystis Using Digital-Droplet-Polymerase-Chain-Reaction-Based Multiplex Assay - In-Su Kim; Hae-Kyung Park (Toxins)
The proliferation of harmful cyanobacteria, particularly Microcystis, poses significant risks to drinking and recreational water resources, especially under the influence of climate change. Conventional monitoring methods based on microscopy for harmful cyanobacteria management systems are limited in detecting toxigenic genotypes, hindering accurate risk assessment. In this study, we developed a digital droplet PCR (ddPCR)-based method for the simultaneous quantification of total and toxigenic Microcystis in freshwater environments. We targeted the secA gene, specific to the Microcystis genus, and the mcyA gene, associated with microcystin biosynthesis. Custom-designed primers and probes showed high specificity and sensitivity, enabling accurate detection without cross-reactivity. The multiplex ddPCR assay allowed for concurrent quantification of both targets in a single reaction, reducing the analysis time and cost. Application to field samples demonstrated good agreement with microscopic counts and revealed seasonal shifts in toxigenic genotype abundance. Notably, ddPCR detected Microcystis at very low densities—down to 7 cells/mL in the mixed cyanobacterial communities of field samples—even when microscopy failed, highlighting its utility for early bloom detection. This approach provides a reliable and efficient tool for monitoring Microcystis dynamics and assessing toxin production potential, offering significant advantages for the early warning and proactive management of harmful cyanobacterial blooms.